2021
DOI: 10.31033/ijemr.11.6.12
|View full text |Cite
|
Sign up to set email alerts
|

Does Technostress Impact On University Students’ Academic Performance in the New Normal?

Abstract: Technostress is a critical disease in the current competitive environment experienced by all of us with the rapid enhancement in technology. COVID-19 pandemic has changed people’s lives to blend more with technology. Earlier, organizations and employees used more technology compared to school & university students. But now students have to use technology to do their studies, maintain their association with friends and to spend their leisure time as well. Moreover, every private and public educational inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…A conceptual framework by (Perera, 2021) outlined that techno-overload, techno-invasion, technocomplexity, techno-insecurity and techno-uncertainty as all being linked and negatively affecting academic performance, as a result of digital literacy, accessibility and lack of ICT skills. A study by (Essel et al, 2021) further supports this as their study also outlined digital literacy was also highlighted as major causes of technostress.…”
Section: Technostress In Educational Settingmentioning
confidence: 99%
“…A conceptual framework by (Perera, 2021) outlined that techno-overload, techno-invasion, technocomplexity, techno-insecurity and techno-uncertainty as all being linked and negatively affecting academic performance, as a result of digital literacy, accessibility and lack of ICT skills. A study by (Essel et al, 2021) further supports this as their study also outlined digital literacy was also highlighted as major causes of technostress.…”
Section: Technostress In Educational Settingmentioning
confidence: 99%
“…This is studied under the term "technostress", which is stress experienced by individuals due to the use of ICTs [53]. Although some researchers agree that younger generations are digital natives and possess significant technological talent [11,49], studies have shown that they are not immune to experiencing technostress [79]. To attend classes and obtain course-related information, students need to allocate an increased amount of time to using their devices and accessing internet platforms that are utilized by educational institutions.…”
Section: Introductionmentioning
confidence: 99%